The Woman Who Saw the Devil: Gender Representations in Brazil's Cordel Narratives - Kateřina Březinová (Gender a Výzkum)
This article focuses on the cordel as an idiosyncratic manifestation of Brazilian popular culture. It sets the results of original research on cordel gender representations within the specific social, cultural, and political contexts in which they originated/emerged. The article is based on research grounded in cultural studies and this discipline's insistence on the critical importance of race, gender, and religion. The author argues that cordels - poems printed in cheap booklets with an illustrated cover and marketed to the mass public - offer important insights into existing social and gender norms in Brazil. Whereas in the past the genre was dominated by men authors and upheld conservative Catholic values, nowadays it has creatively adapted to the changing social realities. A comparative analysis of specific titles written in rural Brazil in the second half of the 20th century and titles written in the early 21st century by emerging women authors in an urban setting reveals starkly different patterns of gender representation. Contemporary authors - many of them women - are well aware of the cordel's importance as a tool in the socialisation and apprehension of cultural meanings of gender. They represent gender through the cordel in ways that are subversive and serve to undermine the existing patriarchal norm. The cordel today continues to develop into a genre which is open and pluralistic in its multiple gender representations that reflect Brazil's diverse social realities.